PERAN GURU TERHADAP TUTOR SEBAYA DALAM PEMBELAJARAN MATEMATIKA PADA SISWA KELAS IV SD - Albarashwa Puteri, Anida Aulia; Daniarista, Meyra; Nurhaeti, Suci (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to learn more deeply about the role of teachers in the application of peer tutoring methods, especially in math studies in grade IV elementary school. The research method used is descriptive qualitative research.Research results show that teachers play a role in the application of peer tutoring methods to mathematical learning as facilitators and mentors. And it shows that teachers play a significant role in organizing and supporting the success of peer tutoring methods.